WORKING CAPITAL, OPERATIONAL COSTS, INVENTORY TURNOVER AND TOTAL DEBT AS PREDICTOR VARIABLES ON NET INCOME - Nurkholik Nurkholik; Ageng Prasetyo; Siti Pujiati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to examine the effect of working capital, operating costs, inventory turnover, and total debt on net income in textile and garment industry sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The sample of this study were 13 companies with an observation period of 5 years. The sampling technique used is purposive sampling, with a total research data of 57. The dependent variable (bound) in this study is net income. The independent variables (independent) in this study are working capital, operating costs, inventory turnover, and total debt. The statistical method used is multiple linear regression analysis by testing the classical assumptions first using the SPSS Version 25 program. The results show that partially working capital has an effect on net income, operating costs have no effect on net income, inventory turnover has no effect on net income. , total debt affects net income. However, simultaneously, working capital, operating costs, inventory turnover, and total debt affect net income.